2004
DOI: 10.2475/ajs.304.4.333
|View full text |Cite
|
Sign up to set email alerts
|

Extra-basinal fluid infiltration, mass transfer, and volume strain during folding: Insights from the Idaho-Montana thrust belt

Abstract: Finite strain and geochemical variations along strain gradients were used to study cleavage development in carbonates in the Lost River Range, Idaho. Deformation accommodating layer-parallel shear was partitioned into thin deformation zones during folding of Willow Creek anticline. Cleavage intensity is strong to very strong in deformation zones and weak in surrounding rocks. Strain magnitudes range from e s ‫23.0؍‬ (1.15:0.93:0.73; x, y, z, principal axes of strain) outside, to e s ‫46.0؍‬ (1.29:0.80:0.52) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 108 publications
(96 reference statements)
0
17
0
Order By: Relevance
“…(1998), Bebout et al. (2001), and Anastasio et al. (2004) further west within the Montana recess showed that veins formed during Sevier deformation could vary in isotopic composition based on the amount of upstream fluid–rock interaction ( δ 18 O = +5 to +27‰).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…(1998), Bebout et al. (2001), and Anastasio et al. (2004) further west within the Montana recess showed that veins formed during Sevier deformation could vary in isotopic composition based on the amount of upstream fluid–rock interaction ( δ 18 O = +5 to +27‰).…”
Section: Discussionmentioning
confidence: 99%
“…Isotopic results suggest that meteoric fluids infiltrated into the Sevier thrust sheets to the basal décollement along the thrust front to depths of at least 4 km in southwest Montana and 7–10 km in the Lost River Range, Idaho (Bebout et al. 2001; Anastasio et al. 2004).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations